Dual Effects of Sulfated D-galactans from the Red Algae Botryocladia occidentalis Preventing Thrombosis and Inducing Platelet Aggregation - Farias, Wladimir R. L.; Nazareth, Rômulo A.; Mourão, Paulo A. S. (Thrombosis and Haemostasis, 2001)
Sulfated D-galactans occur on the red algae Botryocladia occidentalis as three fractions that differ in their sulfate content. Fractions F2 and F3 are potent anticoagulants. Like heparin, they enhance thrombin and factor Xa inhibition by antithrombin and/or heparin cofactor II. The inhibition potency increases simultaneously with the sulfate content of the fractions. The antithrombotic activity of these sulfated D-galactans was investigated on an experimental thrombosis model in which thrombus formation was induced by a combination of stasis and hypercoagulability. In contrast with heparin, the sulfated D-galactans showed a dual dose-response curve preventing thrombosis at doses up to0.5 mg/ kg body weight but losing the effect at higher doses. This unexpected behavior is probably due to a combined action of the sulfated D-galactan as anticoagulant and also as a strong inducer of platelet aggregation. In platelet-depleted animals the antithrombotic activity at higher dose of sulfated D-galactan is restored and almost total inhibition of thrombus formation is achieved. The sulfated D-galactan has no hemorrhagic effect even at high doses, possibly as a consequence of its effect on platelet aggregation. At comparable dose heparin has an intense bleeding effect. These results indicate that new polysaccharides, with well-defined structures, can help to distinguish events, such as antithrombotic and anticoagulant activities, bleeding and platelet-aggregating effects, which are obscure when induced simultaneously by a single compound.
Keywords: Sulfated galactan; antithrombotic action; anticoagulant activity; algal polysaccharide; platelet aggugation